Revisión de literatura con análisis bibliométrico de la cadena de suministro hospitalaria - Ruíz-Orjuela, Erika Tatiana; Gatica-González, Gustavo; Adarme-Jaimes, Wilson (Ingeniería, 2023)
Context: The healthcare sector has continuously faced the challenges of reducing costs and improving quality of care. Research on the supply chain in the health sector has aroused a higher level of interest in the scientific community. Several articles have been published on the subject, focusing on aspects such as chain performance, management approaches, inventory management, supplier evaluation and selection, and some others with broader areas of focus. Method: This article presents a literature review and a bibliometric analysis. The analysis begins by identifying studies published in the last ten years. Then, bibliometric tools are used to identify key research topics, their interrelationships, and patterns of collaboration. Results: This research helps to graphically illustrate publications on hospital supply chain management, present their evolution over time, and identify areas of current research interest and possible lines of research for the future. The results identify the state of development and the main trends in terms of impact, main journals, articles, topics, authors, and countries. Conclusions: Future research can focus on more innovative studies from multiple dimensions: supply chain, management and organization, health services, operations management, sustainability, performance, context, and trends.